Campylobacter jejuni in Different Canine Populations: Characteristics and Zoonotic Potential - Maria-Leonor Lemos (MDPI AG, 2021)
With most epidemiological studies focused on poultry, dogs are often overlooked as a reservoir of Campylobacter, even though these animals maintain close daily contact with humans. The present study aimed to obtain a first insight into the presence and characteristics of Campylobacter spp. in different canine populations in Portugal, and to evaluate its zoonotic potential through genomic analysis. From a total of 125 rectal swabs collected from companion (n = 71) and hunting dogs (n = 54) living in two different settings, rural (n = 75) and urban (n = 50), 32 Campylobacter spp. isolates were obtained. Four different Campylobacter species were identified by Multiplex PCR and MALDI-TOF mass spectrometry, of which Campylobacter jejuni (n = 14, 44%) was overall the most frequently found species. Relevant resistance phenotypes were detected in C. jejuni, with 93% of the isolates being resistant to ciprofloxacin, 64% to tetracycline, and 57% to ampicillin, and three isolates being multi-drug-resistant. Comparison of the phenotypic and genotypic traits with human isolates from Portuguese patients revealed great similarity between both groups. Particularly relevant, the wgMLST analysis allowed the identification of isolates from human and dogs without any apparent epidemiological relationship, sharing high genetic proximity. Notwithstanding the limited sample size, considering the high genomic diversity of C. jejuni, the genetic overlap between human and dog strains observed in this study confirmed that the occurrence of this species in dogs is of public health concern, reinforcing the call for a One Health approach.